Across the great limit. Urban heterotopies, cinema and literature - A. del Valle, Luis; Centro Grupo de Estudios Amancio Williams. Facultad de Arquitectura, Diseño y Urbanismo. Universidad de Buenos Aires. Calle Intendente Güiraldes 2160 Pabellón III 4º piso. Ciudad Universitaria. (C1428EGA) Ciudad Autónoma de Buenos Aires. (Instituto de Arte Americano e Investigaciones Estéticas “Mario J. Buschiazzo”, 2015)
The history of Modernity is, in a certain way, the history of the other, the place of the otherness, the conflict, the non agree. Against its own tendency to conform an order, and a group of taxonomies, that try to explain the world, the same modernity has exacerbated in the drive of revolving itself against its own principles, or the idea of a destiny. In this display, and as Foucault would believe, the great utopias of the modern project have been contrasted by the heterotopias, those other spaces that put into discussion their own criteria of place. As a complement, and at the same time as a critical manner towards architecture, literature or cinema have investigated and exposed these anti-spaces, these unhabitables that impeached the order of things.